2011
DOI: 10.1111/j.1399-3046.2011.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in children and adolescents with kidney transplants

Abstract: Hypovitaminosis D is highly prevalent in adult kidney-transplanted patients. The knowledge of vitamin D status in kidney-transplanted children and adolescents is sparse. The present study investigated the vitamin D status of a cohort of kidney-transplanted children and adolescents, and the association between vitamin D status and plasma concentrations of PTH, ionized calcium, and phosphate. The study included 35 patients with a functioning graft. Their mean age was 12.0 yr, and the mean graft age was 2.8 yr. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
(41 reference statements)
1
5
1
1
Order By: Relevance
“…We found a high prevalence of hyperparathyroidism early in CKD and demonstrated a significant relationship between 25(OH)D and PTH regardless of calcitriol level, consistent with the findings of Shroff et al in a study of pediatric renal transplant recipients [24] and with those of Brodersen et al [12]. This finding underscores the fact that the disordered mineral metabolism starts early in CKD and may contribute to the difficulty in controlling the disorder in later stages of the disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found a high prevalence of hyperparathyroidism early in CKD and demonstrated a significant relationship between 25(OH)D and PTH regardless of calcitriol level, consistent with the findings of Shroff et al in a study of pediatric renal transplant recipients [24] and with those of Brodersen et al [12]. This finding underscores the fact that the disordered mineral metabolism starts early in CKD and may contribute to the difficulty in controlling the disorder in later stages of the disease.…”
Section: Discussionsupporting
confidence: 91%
“…There are few studies to date examining the prevalence of vitamin D deficiency or insufficiency in the context of CKD [7, 1215]. Because of the potential for a lack of 25(OH)D substrate compromising the ability to produce sufficient 1,25(OH) 2 D, it may be important to evaluate both 25OHD and 1,25(OH) 2 D levels in the CKD population.…”
Section: Introductionmentioning
confidence: 99%
“…A moderate‐fat diet with an emphasis on healthy fats such as olive oil, fish, and nuts is indicated with hyperlipidemia, and lipid profiles should be monitored regularly. Brodersen et al 28 reported a high prevalence of hypovitaminosis D (54%) in a population of 35 pediatric kidney transplanted patients. Vitamin D deficiency in children with renal failure may be the result of renal insufficiency, as the kidney transforms the circulating form of vitamin D (25‐dihydroxyvitamin D) into the biologically active form (1,25‐dihydroxyvitamin D), and lack of sun exposure.…”
Section: Nutrition Requirementsmentioning
confidence: 99%
“…Although every patient who receives a renal transplant by definition has CKD, the treatment of CKD complications is not implemented with the same rigor for all renal transplant patients [ 4 ]. One of the modifiable risk factors is the correction of vitamin D deficiency, which is highly prevalent among pediatric renal transplant recipients [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%